Detectability of circulating microRNAs in microRNA extracts with low purity and yield using quantitative real-time polymerase chain reaction: Supporting evidence - Ahmad, Azmir; Kaderi, Mohd. Arifin; Tumian, Afidalina; Sivanesan, Vijaya Mohan; Abdullah, Kahairi; Leman, Wan Ishlah; Mohamad, Irfan; Wan Zainon, Wan Mohd. Nazri; Mohd. Shiyuti, Muhammad Izani; Mohamed Awang, Kamariah; Rosla, Luqman; Paul, Mark; Syed Yussof, Sharifah Nor Ezura; Ramli, Rosdi (UI Scholars Hub, 2020)
Background: Circulating microRNAs (miRNAs) are a group of noncoding RNAs with promising potential as minimal invasive biomarkers for noncommunicable diseases. However, challenges exist in the preparation of these miRNAs from peripheral blood samples for quantification purposes. The low quality of miRNA extracts presents an obstacle. Acknowledging the superior performance of quantitative real-time polymerase chain reaction (qPCR) as gold standard for gene expression analysis, we conducted this study to observe the capabilities of qPCR using the Taqman® protocol in amplifying circulating miRNAs from miRNA extracts with low purity and yield. Methods: miRNAs were extracted from thirty-six plasma samples that were obtained from public subjects. Four selected miRNAs were quantified using the Taqman® protocol in an integrated fluidic circuit chip that was optimized from a previous study. The amplification graph and Cq values were obtained to observe any abnormal amplification signs and expression levels, respectively. Results: The qualitative observation of the amplification of the four miRNAs showed no sign of abnormality, thereby indicating the successful amplification of the miRNAs without enzymatic inhibition. Furthermore, the miRNAs were quantified in high expression levels. Conclusion: The circulating miRNA extracts with low purity and yield were practical for the study of circulating miRNA expression based on the Taqman® protocol as the method of detection.